1996
DOI: 10.1111/j.1467-8624.1996.tb01804.x
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers' Emotional Control in the Disappointment Paradigm and Its Relation to Temperament, Emotional Knowledge, and Family Expressiveness

Abstract: The present research evaluated a conceptual model that links temperament, emotional knowledge, and family expressiveness to preschoolers' emotion regulation ability. The emotional understanding of 82 preschoolers was assessed with 2 separate tasks. After the second emotional knowledge task, the children were presented a "disappointing" prize, and their facial displays of positive and negative affect were recorded. The children and their mothers also participated in a game designed to elicit maternal expressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 59 publications
4
26
1
1
Order By: Relevance
“…Given that the variance in the children’s scores in the current study was primarily due to factors within rather than between the classrooms, and given that past research has already found strong associations with parental emotion socialization practices and children’s emotional competence (Denham & Grout, 1992; Denham & Kochanoff, 2002; Denham et al, 1997; Denham et al, 1994; Fabes et al, 2002; Garner et al, 1994; Garner & Power, 1996; Garner et al, 1997), it would have been informative to know what kinds of emotion socialization strategies were being employed in the children’s home environments.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Given that the variance in the children’s scores in the current study was primarily due to factors within rather than between the classrooms, and given that past research has already found strong associations with parental emotion socialization practices and children’s emotional competence (Denham & Grout, 1992; Denham & Kochanoff, 2002; Denham et al, 1997; Denham et al, 1994; Fabes et al, 2002; Garner et al, 1994; Garner & Power, 1996; Garner et al, 1997), it would have been informative to know what kinds of emotion socialization strategies were being employed in the children’s home environments.…”
Section: Discussionmentioning
confidence: 83%
“…For example, research has shown that children’s skill at theory of mind tasks (Harwood & Farrar, 2006) and temperamental characteristics, such as dispositional emotional intensity (Garner & Power, 1996) and fearfulness (van der Mark, van Ijzendoorn, & Bakermans-Kranenberg, 2002), are associated with their emotional competence. Furthermore, children’s temperamental characteristics have been found to interact with emotional support in predicting academic outcomes (Curby, Rudasill, Edwards, & Perez-Edgar, 2011), and to influence mothers’ socialization behaviors (Eisenberg & Fabes, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Of these few, findings do suggest a link between this component of the family context and children's ER. For example, Garner and Power (1996) found that negative maternal expressiveness was related to lower levels of children's expressed negative emotions during a disappointment task. In a study conducted by Eisenberg, Gershoff, et al.…”
Section: The Family Context and Emotion Regulationmentioning
confidence: 99%
“…Generally, parents who display a lot of positivity have children who are also positive in their expressiveness (Camras et al ., ; Cassidy, Parke, Butkovsy, & Braungart, ; Isley, O'Neil, Clatfelter, & Parke, ) Results are more complex for parents' expression of negative emotion. Mothers' expression of negative emotion has been associated with less positive expression by children in one study (Garner & Power, ), and more positive expression in another (Cassidy et al ., ). It has also been suggested that mothers and children tend to display similar amounts of negative emotion during play, whereas father–child dyads tend to display dissimilar amounts (Isley et al ., ).…”
mentioning
confidence: 99%